Lead (Pb) removal from gold mining-impacted water utilizing palm oil fuel ash (POFA) - Heraningsih, Sarah Fiebrina; Rainiyati, Rainiyati; Riduan, Ahmad; Viareco, Hariestya; Jasminarni, Jasminarni; Novita, Trias (Journal of Degraded and Mining Lands Management, 2024)
Mining, particularly gold mining, is a lucrative industry. However, it poses significant environmental risks, such as releasing heavy metal elements into the soil and water. After gold mines are exhausted, whether they are small or large scale, the excavated sites often need to be repaired. This situation has led to a global concern regarding the presence of heavy metals from mining activities, which are known to be carcinogenic and harmful to living organisms. The concentration of heavy metals in these areas often surpasses safety limits, necessitating advanced treatment methods for their removal, especially lead (Pb) compounds from gold mining waste. One effective treatment method is the adsorption process. This study examined POFA's inherent capacity to remove lead from water contaminated by gold mining without modification. This method was preferred due to its high efficiency and cost-effective option for removing heavy metal compounds. According to the experiment's results, the largest adsorption capacity of 0.816 mg/g was followed by the greatest removal efficiency of 91.837%. The isotherm analysis found that the Langmuir model provided an outstanding fit for the experimental data. Thus, this relationship suggested that on the surface of the POFA, a monolayer and an adsorption process suitable for physical adsorption took place.